2008
DOI: 10.1007/s11814-008-0179-y
|View full text |Cite
|
Sign up to set email alerts
|

A CFD model for predicting the flow patterns of viscous fluids in a bioreactor under various operating conditions

Abstract: Computational fluid dynamics simulation is becoming an increasingly useful tool in the analysis and design of simultaneous saccharification fermentation (SSF) and saccharification followed by fermentation process (SFF). To understand and improve mixing and mass transfer in a highly viscous non-Newtonian system, it was necessary to simulate the flow behavior in this bench scale bioreactor (BioFlo 3000). This study focused on designing a high concentration medium agitation system for such a process using the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…They found that when using nonhomogeneous and nonlinear pipe materials, the measurement error would depend on the acoustic characteristics of the pipe material [13]. In terms of simulation, Byunghad studied the completely velocity distribution of rotating and swirling turbulent flows in circular pipes by using computational fluid dynamics (CFD) simulation to investigate the effect of distorted flow profiles, especially the effect of out-ofplane double bent pipe on ultrasonic flow metering [14]. Luca et al simulated ultrasonic flow meter by modelling the wave propagation in solids with the equations of linear elasticity and the linearized Euler equations in fluids [15].…”
Section: Introductionmentioning
confidence: 99%
“…They found that when using nonhomogeneous and nonlinear pipe materials, the measurement error would depend on the acoustic characteristics of the pipe material [13]. In terms of simulation, Byunghad studied the completely velocity distribution of rotating and swirling turbulent flows in circular pipes by using computational fluid dynamics (CFD) simulation to investigate the effect of distorted flow profiles, especially the effect of out-ofplane double bent pipe on ultrasonic flow metering [14]. Luca et al simulated ultrasonic flow meter by modelling the wave propagation in solids with the equations of linear elasticity and the linearized Euler equations in fluids [15].…”
Section: Introductionmentioning
confidence: 99%
“…There are many different definitions of the word "biorefinery," but the term is generally applied to the use of renewable raw materials (e.g,, biomass) to produce energy, together with a wide range of everyday commodities, in an economic and sustainable manner [2][3][4][5]. The biorefinery concept applies the methods that have been used to refine petroleum to biomass conversion [3]. Biorefineries simultaneously produce biofuels, biobased chemicals, heat, and power.…”
Section: Introductionmentioning
confidence: 99%
“…Acetic acid is a normal end-product of alcoholic fermentation in the biorefinery process, and can also be formed by Saccharomyces cerevisiae; additional amounts may be produced after alcoholic fermentation by lactic acid bacteria [2][3][4][5] and/or acetic acid bacteria [6]. The concentration of acetic acid produced during alcoholic fermentation may vary with the species of strains [7,8], the composition of hydrolysates [9], and other physical factors [10,11].…”
Section: Introductionmentioning
confidence: 99%